PENGARUH PENGGUNAAN MODEL PEMBELAJARAN AIR (AUDITORY, INTELLECTUALY, REPETITION) BERBANTU QUESTION CARD TERHADAP HASIL BELAJAR IPS TERPADU PESERTA DIDIK KELAS VII SMP MUHAMMADIYAH AHMAD DAHLAN - Rahmadani Hasanah; Ningrum Ningrum (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The problems that exist during the learning process are still found students who do not play an active role, are slow in accepting the material presented by the teacher. This study aims to determine the effect of using the AIR learning model (Auditory, Intellectualy, Repetition) assisted by a question card on the learning outcomes of grade VII students of SMP Muhammadiyah Ahmad Dahlan Metro in 2020/2021. This research is the result of quantitative analysis with a quasi-experimental type, with a design that is Non-equivalent Control Group Design. Based on the research results, through the calculation of the t-test formula using the two mean similarity test level with a significant level of 5%. To test the hypothesis using the Simple Linear Registration formula, Y = 56,7123 + 0,3214 then continued with tvalue is = 1,64. Ttab = 1,701, with the significant of 5% to 1,64 > 1,701 then the hypothesis is accepted. So it can be concluded that there is a significant effect of the AIR (Auditory, Intellectually, Repetition) instructional model use assisted with question card on integrated Social Science instructional outcomes of grade VII students of Muhammadiyah Ahmad Dahlan Junior High School of in 2020/2021 academic year.